Female Obesity and Assisted Reproductive Technologies - Kumbak, Banu; Oral, Engin; Bukulmez, Orhan (Thieme Medical Publ Inc, 2012)
Obesity has grown to epidemic proportions, and currently nearly half of the reproductive-age women are overweight or obese. Risks, success rates, and economic aspects of infertility treatments in obese women have been extensively investigated. Unfavorable ovarian stimulation characteristics like increased gonadotropin consumption, fewer selected follicles, and lower number of retrieved oocytes have been observed in obese women undergoing assisted reproductive technologies (ART). There seems to be a strong association between increased body mass index and lower pregnancy and live-birth rates and increased miscarriage rate. Coexisting factors like age and polycystic ovary syndrome status have also been blamed for these adverse effects. The mechanisms underlying those adverse outcomes, whether ovarian or endometrial, still remain to be fully elucidated. Moreover, maternal, perinatal, and neonatal complications have also been reported to be higher in obese pregnant women. Hence in some countries strict restrictions exist for access to elective fertility treatment in obese women. However, it is controversial if these policies are socially and ethically acceptable. Furthermore, because weight reduction is not an easy task, it may lead to the decreased probability of conception due to the advancing reproductive age for many obese women. Thus weight reduction should be encouraged and patients counseled accordingly, but whether restriction for fertility treatment is implemented in obese women remains a matter of debate. There remains much to be known regarding the association between obesity and ART.
Keywords: obesity; body mass index; ART; IVF; outcome